Desenvolvimento de um novo implante utilizado no tratamento de lesões do manguito rotador - Guimarães, Marcília Valéria (2013)
The rotator cuff tears generate functional disability and shoulder pain and their possible causes are related to acute trauma, tendon degeneration and subacromial impingement. The surgical treatment is performed through arthroscopy using suture anchors. These implants can be metallic or non-metallic and have suture threads. The main purpose of soft tissue fixation devices is to achieve a close approximation between the tendon and the bone to allow the former to heal securely to the latter. However, the disadvantage of this technique is the difficulty of guiding sutures through tendon and tying secure knots resulting in increased surgical time and costs. For this reason sutureless screw anchors were developed, however, there are little data regarding the mechanical properties or clinical outcomes of how well these implants perform in rotator cuff repairs. The main aim of this study was to develop an alternative implant to suture anchors, which does not use suture threads and can be applied directly and quickly to reattach tendons to bone. The proposed implant was designed in the shape of a titanium staple. The tendon attachment to the humerus with this new device is made by a cross-bar portion of the staple and the pull out strength is provided by the barbs disposed at the legs of the staple. The new implant was evaluated to check its strength and stability in rotator cuff repairs using finite element analysis. To carry out the numerical simulations it was necessary to determine parameters of forces acting on the attachment of the tendon to the bone through tensile tests using bovine tendon and humerus specimens. The predicted forces were used as the basis to determine the loading conditions of the rotator cuff repair with the new device. A finite element model of repair with suture anchor was also made to understand the physical phenomenon of the tie sutures process. The simulation considering both attachment implants using a simplified three-dimensional model of the humerus and supraspinatus tendon carried out. The results of the simulation showed that the staple, under the analyzed conditions, provided a stable fixation of tendon to bone.